(untitled) (MCIT: Proceedings of International scientific and practical conference, 2021)
Just a few decades ago, books were mostly used as educational media, while posters, various mechanical models, etc. were used as educational visual illustrations. Laboratory experiments for teaching chemistry, physics, biology, etc. were conducted in schools and colleges using real materials. Today the situation is drastically changed and all this has been forgotten. Modern computer teaching technologies are being rapidly introduced in the educational space replacing old tehcnology with hypertexts, e-books and textbooks, tutorials and many other forms and contents.